Tracheal Resection after Previous Treatment Provides Comparable Outcome to Primary Surgery - Slama, Alexis; Zaatar, Mohamed; Demir, Muhittin; Okumus, Oezlem; Mattheis, Stefan; Kampe, Sandra; Darwiche, Kaid; Lang, Stephan; Aigner, Clemens (The Thoracic and Cardiovascular Surgeon, 2021)
Background Tracheal and laryngotracheal surgery provides both excellent functional results and long-term outcomes in the treatment of tracheal stenosis. Consequently, challenging re-resections are rarely necessary. The purpose of this study was to compare the outcome of (laryngo-)tracheal re-resection and surgery after bronchoscopic interventions with that of primary surgery.Methods Patients undergoing resection for benign tracheal stenosis at our center between 1/2016 and 4/2020 were included. Perioperative characteristics and functional outcomes of patients were used for statistical analysis.Results Sixty-six patients who underwent (laryngo-)tracheal resection were included (previous resection [A = 6], previous stent [B = 6], previous bronchoscopic intervention w/o stenting [C = 19], untreated [D = 35]). Baseline parameters were largely comparable between groups with exception from group B that had significantly worse lung function. Group A necessitated more complex reconstructions (end-to-end: n = 1: 17%| cricotracheal n = 2: 33%| cricotracheal with mucosectomy n = 2: 33%| laryngoplasty: n = 1: 17%) than patients in group D (end-to-end n = 21: 60%| cricotracheal n = 14: 40%). Postoperative outcomes were comparable throughout groups (intensive care unit: 1[1–18] days; hospital stay: 8[5–71] days). Anastomotic complications were higher after previous stenting (A: 0%; B: 33.3%; C: 10.5%; D: 2.9%; B/D p = 0.008| surgical revisions: A: 16.7%; B: 33.3%; C: 0%; D: 5.7%; B/D, p = 0.035). Overall, postoperative lung function was significantly better (forced expiratory volume in 1 second: 63% ± 24 vs. 75% ± 20; p = 0.001 | PeakEF 3.3 ± 1.9 vs. 5.0 ± 2.2L; p = 0.001). No 90-day mortality was observed in any group. Median follow-up was 12(1–47) months.Conclusion In carefully selected patients treated in a specialized center, tracheal or laryngotracheal resection after previous tracheal interventions provides comparable outcome to primary surgery.
Keywords: trachea; airway; larynx